Ecological implications of hypoxia‐triggered shifts in secondary metabolism. (21st March 2017) - Gallagher, Kelley A.; Wanger, Greg; Henderson, Jane; Llorente, Mark; Hughes, Chambers C.; Jensen, Paul R.
Summary: Members of the actinomycete genus Streptomyces are non‐motile, filamentous bacteria that are well‐known for the production of biomedically relevant secondary metabolites. While considered obligate aerobes, little is known about how these bacteria respond to periods of reduced oxygen availability in their natural habitats, which include soils and ocean sediments. Here, we provide evidence that the marine streptomycete strain CNQ‐525 can reduce MnO2 via a diffusible mechanism. We investigated the effects of hypoxia on secondary metabolite production and observed a shift away from the antibiotic napyradiomycin towards 8‐amino‐flaviolin, an intermediate in the napyradiomycin biosynthetic pathway. We purified 8‐amino‐flaviolin and demonstrated that it is reversibly redox‐active (midpoint potential −474.5 mV), indicating that it has the potential to function as an endogenous extracellular electron shuttle. This study provides evidence that environmentally triggered changes in secondary metabolite production may provide clues to the ecological functions of specific compounds, and that Gram‐positive bacteria considered to be obligate aerobes may play previously unrecognized roles in biogeochemical cycling through mechanisms that include extracellular electron shuttling.